The risk of extrapolation in neuroanatomy: the case of the mammalian vomeronasal system - Ignacio Salazar; Pablo Sánchez Quinteiro (Frontiers Media S.A., 2009)
The sense of smell plays a crucial role in mammalian social and sexual behaviour, identification of food, and detection of predators. Nevertheless, mammals vary in their olfactory ability. One reason for this concerns the degree of development of their pars basalis rhinencephali, an anatomical feature that has has been considered in classifying this group of animals as macrosmatic, microsmatic or anosmatic. In mammals, different structures are involved in detecting odours: the main olfactory system, the vomeronasal system (VNS), and two subsystems, namely the ganglion of Grüneberg and the septal organ. Here, we review and summarise some aspects of the comparative anatomy of the VNS and its putative relationship to other olfactory structures. Even in the macrosmatic group, morphological diversity is an important characteristic of the VNS, specifically of the vomeronasal organ and the accessory olfactory bulb. We conclude that it is a big mistake to extrapolate anatomical data of the VNS from species to species, even in the case of relatively close evolutionary proximity between them. We propose to study other mammalian VNS than those of rodents in depth as a way to clarify its exact role in olfaction. Our experience in this field leads us to hypothesise that the VNS, considered for all mammalian species, could be a system undergoing involution or regression, and could serve as one more integrated olfactory subsystem.